2003
DOI: 10.4161/cc.2.3.403
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Instability, DNA Damage and Atherosclerosis

Abstract: We review the role of somatic mutations and genetic instability in the pathogenesis of atherosclerosis, suggesting novel therapeutic approaches.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 41 publications
0
8
0
Order By: Relevance
“…Oxidative damage to DNA is implicated in atherogenesis (25)(26)(27), but the underlying pathways remain undefined. Our detection of elevated levels of 5-chlorouracil in human atherosclerotic lesions implicates myeloperoxidase as one potential mechanism.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Oxidative damage to DNA is implicated in atherogenesis (25)(26)(27), but the underlying pathways remain undefined. Our detection of elevated levels of 5-chlorouracil in human atherosclerotic lesions implicates myeloperoxidase as one potential mechanism.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, somatic mutations may play other roles in atherogenesis as recent studies have linked chromosomal abnormalities, loss of heterozygosity, and microsatellite instability to human atherosclerosis (reviewed in Ref. 27). …”
mentioning
confidence: 99%
“…It has been suggested that oxidative stress may contribute to this, and other, mtDNA deletion events and its occurrence in PBMC suggests a more global oxidative stress in the vasculature of these patients [22]. The common mtDNA deletion also accumulates suggestions from the literature would indicate that carcinogenesis and atherosclerosis may share common molecular processes, with a potential pathogenic role for DNA damage [23] In this case, this raises the possibility of (oxidative) DNA damage inducing mutation, conferring survival/growth advantages and assisting the clonal expansion of selected vascular smooth muscle cells, for example [24]. This latter area and that of the examination of somatic mutations in CVD, is receiving notable research attention, not to the detriment of the widely accepted inflammation hypothesis of atherosclerosis, but as a complement to this.…”
Section: Cardiovascular Diseasementioning
confidence: 99%
“…Inflammation and fibrosis in various organs, albeit at relatively high dose levels, is a well-documented effect of irradiation of vascular endothelial cells as a pathologic response (Kachnic & Powell 2002), and as a persistent condition in atomic bomb (A-bomb) survivors (Neriishi 1999). It is generally agreed that radiation at high doses can exacerbate or induce atherosclerosis (and associated myocardial infarction), an inflammatory disease of the intimal layer of arteries characterised by fibrotic, lipid-containing plaques (Andreassi & Botto 2003, Hoel 2006). The evidence is less convincing for a positive association between low and moderate radiation doses (55 Gy) and late-occurring CVD, including that from Abomb survivor studies (Little et al 2008).…”
Section: Introductionmentioning
confidence: 98%